Structure and absolute configuration of a secolignan from Peperomia blanda - Felippe, Lidiane G. [UNESP]; Batista, Joao M. [UNESP]; Baldoqui, Debora Cristina [UNESP]; Nascimento, Isabele Rodrigues [UNESP]; Kato, Massuo J.; Bolzani, Vanderlan da Silva [UNESP]; Furlan, Maysa [UNESP] (Elsevier B.V., 2011)
A secolignan, (-)-2-methyl-3-[bis(3 ',4 '-methylenedioxy-5 '-methoxyphenyl) methyl] butyrolactone (1), with a rare cis configuration was isolated from the aerial parts of Peperomia blanda (Piperaceae). The structure of this compound was elucidated by a combination of spectroscopic methods, including ultraviolet, infrared, 1D- and 2D- nuclear magnetic resonance as well as high resolution mass spectrometry data. The absolute configuration of (-)-1 was determined as (2R,3S) by the comparison of experimental electronic circular dichroism (ECD) spectroscopy and time-dependent density functional theory (TDDFT) calculations. (C) 2011 Phytochemical Society of Europe. Published by Elsevier B.V. All rights reserved.
Keywords: Peperomia blanda; Piperaceae; Secolignan; Absolute configuration; Electronic circular dichroism; Density functional theory